The Relationship Between Study Discipline and Pastry Learning Outcomes of Students at SMK Negeri 1 Ampek Angkek - Afriani, Winda; Gusnita, Wiwik; Siregar, Juliana; Andriani, Cici (Universitas Negeri Padang, 2025)
This research was motivated by the low learning outcomes of students in the Pastry subject. One of the factors influencing learning outcomes is learning discipline. The purpose of this study is to describe students' learning discipline, describe their Pastry learning outcomes, and analyze the relationship between the two. This study used a quantitative approach with a correlational method. The population consisted of all Grade XII Culinary students at SMK Negeri 1 Ampek Angkek in the 2023/2024 academic year, comprising 61 students. The sampling technique used was total sampling. Data on learning discipline were collected through a Likert scale questionnaire tested for validity and reliability, while learning outcomes were obtained from students' final exam scores in Pastry. Data analysis was carried out using descriptive and correlation techniques. The t-test results showed that t_count 9.092 > t_table 2.000, thus Ha was accepted and Ho was rejected. It is concluded that there is a positive and significant relationship between learning discipline and learning outcomes.